EPISTEMOLOGICAL POLEMICS IN DIGITAL RELIGION: MAPPING APPROACHES IN THE DIGITAL SPHERE - Rohmatin, Tien; Binaningrum, Banun; Irawan, Bambang; Iman, Muhamad Tamamul; Rahmawati, Firda Devi (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2025)
Digital religion is where religious beliefs meet digital media. Networked technologies have changed how people share, interpret, and practice their faith. These technologies shift authority away from traditional institutions, allowing ordinary people and even algorithms to help create sacred content. Objectives: This study maps and critically analyzes the main debates about religious knowledge online. It proposes frameworks to handle issues of authority, authenticity, and research methods in digital faith settings. Methods: We used a qualitative approach by reviewing scholarly studies, reports, news articles, and online material up to mid‑2025. We applied phenomenological and hermeneutic analyses to examine how digital media are changing the production and understanding of religious knowledge, using case studies from multiple faith traditions. Results: We identified important tensions in digital religion: sacred vs profane spaces; reason vs revelation; authority vs authenticity; insider vs outsider viewpoints; mystical vs empirical knowledge; pluralism vs normativity; and transcendence vs immanence. We also highlight issues such as algorithmic influence, digital inclusion, environmental sustainability, and research challenges. Additionally, we explore new debates on topics like colonialism, gender, and diaspora. We conclude that addressing digital religion requires better religious and digital literacy, inclusive dialogue, ethical technology design, and interdisciplinary research to build a strong, inclusive ecosystem of religious knowledge. By combining existing research with current examples, this article provides a broad overview of the changing knowledge landscape in digital religion.